A Gram Scale Synthesis of 3,4-Dihalogen Substituted 1,8-Naphthalimides - Denitsa Anastasova; Monika Mutovska; Natali Simeonova; Irena Zagranyarska; Zlatina Vlahova; Stanimir Stoyanov; Yulian Zagranyarski (Molbank)
A general protocol for the synthesis of 3,4-dihalogen substituted 1,8-naphthalimides is proposed, starting from available and cheap 1,8-naphthalic anhydride. The reported new compounds have only bromine or chlorine atoms as substituents, in contrast to the known iodo-containing analogues. This is an advantage in possible aryl nucleophilic substitution or cross-coupling modifications, making them interesting and important building-block molecules in naphthalimide chemistry. Although the procedure includes five synthetic steps, they are quick and straightforward. The overall yields are relatively high (48–62%), and only one column of chromatographic purification is needed. All the reactions were carried out on a multigram scale to allow the target building-block compounds to be obtained in sufficient amounts for further derivatizations.